2014
DOI: 10.4238/2014.july.25.5
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of iron regulatory protein-2 on iron metabolism in lung cancer

Abstract: ABSTRACT. Iron metabolism plays an important role in the pathogenesis of lung cancer. This study aimed to investigate the effect of gene silencing of iron regulatory protein-2 (IRP2) on mRNA and protein expression of transferrin (Tf), transferrin receptor (TfR), and ferritin (Fn) in A549 lung cancer cells. A549 cells were cultured and divided into a liposome control group, a liposome + oligonucleotide (SCODN) control group, and a Lipofectamine + antisense oligonucleotide (ASODN) group. RT-PCR and Western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…The top one was IREB2, and then in order of significance, CHRNA3, CHRNA5, HYKK and PSMA4. 28 Silencing of IREB2 in these cells has been shown to modulate the expression of iron metabolism-related genes (transferrin receptor and ferritin) 29 and injection of wild-type IREB2 in mice was shown to stimulate growth of tumor xenografts. 26 IREB2 encodes a RNA-binding protein that regulates iron levels in cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top one was IREB2, and then in order of significance, CHRNA3, CHRNA5, HYKK and PSMA4. 28 Silencing of IREB2 in these cells has been shown to modulate the expression of iron metabolism-related genes (transferrin receptor and ferritin) 29 and injection of wild-type IREB2 in mice was shown to stimulate growth of tumor xenografts. 26 IREB2 encodes a RNA-binding protein that regulates iron levels in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of iron metabolism has been observed in NSCLC 27 and iron has been shown to influence apoptosis of lung cancer cells (A549). 28 Silencing of IREB2 in these cells has been shown to modulate the expression of iron metabolism-related genes (transferrin receptor and ferritin) 29 and injection of wild-type IREB2 in mice was shown to stimulate growth of tumor xenografts. 30 Previous studies have thus demonstrated a potential biological link between IREB2 and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As we do not have the methylation and expression data in the same tissue, we were not able to validate this hypothesis directly, but future integrative studies in lung tissue should elucidate this further. IREB2 gene is coding the RNA-binding protein that binds to iron-responsive elements and can regulate the expression of transferrin receptor and ferritin by changing its own protein expression and thereby regulate iron metabolism, important in pathogenesis of lung diseases [42]. It is shown that IREB2 gene interacts with MYC and MAX genes involved in the regulation of the gene transcription through epigenetic changes [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, overexpression of IRP1 or IRP1 C437S dramatically suppresses the growth of tumor xenografts in nude mice (Chen et al, 2007 ), providing a direct regulatory link between the IRE/IRP system and cancer. In A549 lung cancer cells, IRP2 can regulate the expression of TfR1 and ferritin by changing its own gene expression, and thereby regulating iron metabolism (Cheng et al, 2014 ). Moreover, exhaled ferritin and superoxide dismutase (SOD) have recently been recognized to play a role in lung cancerogenesis and patients’ survival (Carpagnano et al, 2012 ), implying the possibility of using them as an outcome predictor of lung cancer.…”
Section: Iron Is Implicated In a Variety Of Cancer Typesmentioning
confidence: 99%